Pelatihan Aplikasi Assembler Edu Pada Pembuatan Media Pembelajaran Augmented Reality Untuk Guru SD di Sambas - Sitompul, Noferianto; Wijaya, vanie; Mulyanto, U Heri (CV. IRA PUBLISHING, 2025)
Learning media is an essential part of the educational process in schools. Many elementary school teachers still rely on textbooks or PowerPoint slides, resulting in limited variation in teaching materials and reduced student engagement. A lack of training in creating engaging media also contributes to this issue. As a solution, training was provided on developing learning media using augmented reality through the web-based application Assembler Edu. This digital media introduces new and dynamic ways of delivering material, aiming to increase students' interest and motivation in learning. The training outcomes showed that teachers were able to create and present teaching materials using augmented reality, which will be implemented in their respective classrooms.